Matemática, perguntado por yure71p45m8c, 1 ano atrás

Me ajudem, com o cálculo

Anexos:

Soluções para a tarefa

Respondido por ldvtlucas
0
a) ( 2^{3}* 2^{4} * 2^{4} )^{-1} * 2^{5}
    (2^{11})^{-1} * 2^{5}
     \frac{1}{2^{11}} * 2^{5}
     \frac{2^{5}}{2^{11}} = 2^{-6}

b) (3^{2}:3^{4} * 3^{-8})^{2} * 3^{14}
    (3^{-10})^{2} * 3^{14}
    3^{-20} * 3^{14} = 3^{-6}

c)  (2^{7}:2^{6}) : 2^{4}
     2^{1}:2^{4} = 2^{-3}

d)[(10^{-3})^{3}*10^{6}]:10^{-4}
   [ 10^{-9}*10^{6}]:10^{-4}
   10^{-3}:10^{-4} = 10


Perguntas interessantes